2021
DOI: 10.3389/fcell.2021.637675
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Tumor-Stroma Interactions in Drug Resistance Within Tumor Microenvironment

Abstract: Cancer cells resistance to various therapies remains to be a key challenge nowadays. For a long time, scientists focused on tumor cells themselves for the mechanisms of acquired drug resistance. However, recent evidence showed that tumor microenvironment (TME) is essential for regulating immune escape, drug resistance, progression and metastasis of malignant cells. Reciprocal interactions between cancer cells and non-malignant cells within this milieu often reshape the TME and promote drug resistance. Therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
128
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(128 citation statements)
references
References 286 publications
(287 reference statements)
0
128
0
Order By: Relevance
“…In view of the positive correlation between the level of breast density and risk of breast cancer in women, stress-induced breast tumor density might be an indication of promoted degradation of the regular extracellular matrix (ECM) and/or deposition of a tumor-specific ECM in the tumor microenvironment [ 21 ]. As well reviewed by Ni et al, ECM is important for the tumor-stroma interactions within tumor microenvironment [ 22 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…In view of the positive correlation between the level of breast density and risk of breast cancer in women, stress-induced breast tumor density might be an indication of promoted degradation of the regular extracellular matrix (ECM) and/or deposition of a tumor-specific ECM in the tumor microenvironment [ 21 ]. As well reviewed by Ni et al, ECM is important for the tumor-stroma interactions within tumor microenvironment [ 22 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…EMT was regarded as a pivotal step for cancer cells to acquire the ability of migration and invasion ( 39 , 40 ). Moreover, the changes of ECM organization may play a crucial role in tumor recurrence and therapeutic resistance ( 41 , 42 ). The rapid proliferation of cancer cells leads to the formation of hypoxic areas in the tumor center.…”
Section: Discussionmentioning
confidence: 99%
“…The integrative models might better stratify highrisk and low-risk patients, which was beneficial for the treatment of LUAD patients. The potential differences of molecular expression in tumors tend to present as the alterations of tissue structure and nuclear morphology (Madabhushi and Lee, 2016;Ni et al, 2021). Previously, it has been found that STK11, EGFR, FAT1, SETBP1, KRAS, and TP53 mutations of LUAD could be predicted from histopathological images using deep learning (AUCs ranged from 0.733 to 0.856) (Coudray et al, 2018).…”
Section: Discussionmentioning
confidence: 99%